Natural active ingredients used in topical cosmetic formulations for antiageing: a systematic review / Nuramalina Afandi and Shariza Sahudin - Afandi, Nuramalina; Sahudin, Shariza (Faculty of Pharmacy, 2022)
Smooth, even-complexed and radiant skin without wrinkles and dark spots characterizes healthy skin. Ageing is a natural biological process of becoming older. As a largest organ in the body, skin is prone to aging due to exposure to the external and internal damages. Skin ageing is characterized by wrinkles, fine lines and dark spots that appear on the skin surfaces. Cosmetics nowadays not only associated with beauty but also younger looking skin. The demand for antiageing cosmetics with natural ingredients are projected to boost the cosmetics industry contributing to global market growth due to an increase in global ageing populations. There are many cosmetics in the market offered product line for anti-ageing. Despite giving positive result in a longer period, natural ingredients are more preferred as active ingredients compared to synthetic ingredients which are notoriously known for causing complications as mild as minor irritations to more severe anaphylactic reactions, lethal poisonings, or long-time effects to users due to accumulated toxins. In this study, natural active ingredients will be discussed in terms of their sources, mechanisms, and anti-ageing properties. Systematic searches of PubMed, ScienceDirect, NCBI and Medline databases were carried out using various keywords. Through screening, 40 studies out of 70 studies were selected. Based on this review, a large variety of natural active ingredients could be obtained from plants, animals, and marines compared to singly synthesized artificial alternatives. The benefits, safety and efficacy of the ingredients were also evaluated, and it is found that they are indeed better constituents compared to synthetic ingredients to be used in cosmetic formulations.